1983
DOI: 10.1073/pnas.80.8.2107
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evidence that catecholamines are transported across the chromaffin granule membrane as noncationic species.

Abstract: Catecholamines are transported into chromaffin granules by a Mg2+/ATP-driven process under conditions in which the substrate exists primarily as a positively charged or neutral species. In order to distinguish between these two states, we studied the transport properties of a permanently charged quaternary analogue of epinephrine, (R,S)-dimethylepinephrine. We found that this compound was a classical competitive inhibitor of (R)-[3H]norepinephrine uptake, with a K; of 3.8 mM for the racemic form, or 1.9 mM for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Isoproterenol, however, is both a competitive inhibitor and a substrate (19). Thus, the positive charge and not the size of the bulky group around the amine moiety seemed to be responsible for the inability of dimethylepinephrine to be transported across the granule membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isoproterenol, however, is both a competitive inhibitor and a substrate (19). Thus, the positive charge and not the size of the bulky group around the amine moiety seemed to be responsible for the inability of dimethylepinephrine to be transported across the granule membrane.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, the cocaine-sensitive transport of (R)-norepinephrine was inhibited by a series of related compounds with varying efficiencies as defined by IC50. However, dopamine and epinephrine were selected for closer study because of their physiological importance, and isoproterenol and dimethylepinephrine were selected because of previous extensive studies on their transport through the chromaffm granule membrane (19).…”
Section: Uptake Of (R)-[3h]norepinephrine Bymentioning
confidence: 99%
See 2 more Smart Citations
“…At physiologic pH, monoamine substrates for VMAT1 and VMAT2 exist in both neutral and protonated forms. Previous studies had suggested that the transport protein recognizes the neutral form (Ramu et al, 1983). However, more recent work has shown the vesicular transport of permanently charged substrates such as MPP ϩ (Scherman et al, 1988;Daniels and Reinhard, 1988;Moriyama et al, 1993), strongly suggesting that the transporter recognizes the protonated form of monoamine substrates (Schuldiner et al, 1995).…”
Section: Gyiidrvgyeipmentioning
confidence: 98%